Operation and performance of resonant modular multilevel converter with flexible step ratio - Zhang,X; Xiang,X; Green,TC; Yang,X (IEEE Transactions on Industrial Electronics and Control Instrumentation, 2017)
Resonant modular multilevel converters (RMMCs)have been proposed for high voltage dc-dc applications. Using dif-ferent modulation strategies, RMMC operates in different modesand achieves flexible step ratio. To provide a comprehensive studyof RMMCs, this paper presents the modulation method achievinga wide range of step ratio with the ability of inherent-balancing.The conditions for guaranteeing the inherent-balancing abilityare provided. The operation principle and performance of theRMMC are presented in this paper, which have been exploredin a case study. The experimental results are obtained from abench-scale setup, which have verified the theoretical analysis.